التعليل في القرآن الكريم -سورة النساءأنموذجا- - مرزوق, أسامة; مزريقي, محمد الأمين (University of Eloued جامعة الجزائر, 2020)
"تعنى هذه الدراسة بموضوع التعليل في القرآن الكريم- سورة النساء أنموذجا- حاولنا الإلمام ‏بالموضوع من كل جوانبه، وذلك من خلال تقسيم البحث إلى مقدمة ومبحثين وخاتمة.‏ ‏ ذكرنا في المقدمة تمهيد للموضوع إضافة إلى الأهمية وأهداف الموضوع والدراسات السابقة ‏والمنهج المعتمد، والمبحث الأول تناولنا فيه مفهوم التعليل وأوجه وروده في القرآن الكريم، ثم ‏تطرقنا إلى التعريف بسورة النساء.‏ أما المبحث الثاني فقد جعلنا فيه المواضع المختارة من التعليل في سورة النساء سواء التعليل ‏بالمفردات أو الجمل أو الحروف.‏ ثم الخاتمة التي خلصنا فيها إلى أهم النتائج مع بعض التوصيات، ومن أبرز نتائج الدراسة:‏ التعليل من أهم الأساليب البارزة في القرآن الكريم تعددت موضوعاته وتنوعت أغراضه بتنوع ‏صوره في جميع آيات القرآن الكريم، خاصةً سورة النساء.‏""This study deals with the topic of reasoning in the Noble ‎Qur’an - Surat An-Nisa as an example - we tried to get acquainted ‎with the topic from all its aspects, by dividing the research into an ‎introduction, two studies and a conclusion.‎ We mentioned in the introduction a preface to the topic, in ‎addition to the importance and objectives of the topic, previous ‎studies and the approach adopted, and the first topic dealt with the ‎concept of reasoning and its features in the Noble Qur’an, then we ‎touched on the definition of Surat al-Nisa '.‎ As for the second topic, we included in it the selected places of ‎reasoning in Surat Al-Nisaa, whether reasoning in terms, sentences ‎or letters.‎ Then the conclusion, in which we concluded the most ‎important results with some recommendations, and among the most ‎prominent results of the study:‎ Reasoning is one of the most prominent methods in the Noble ‎Qur’an, with its many themes and purposes, in the diversity of its ‎images in all verses of the Holy Qur’an, especially Surat al-Nisa.‎"
مذكرة ماستر تخصص لغة ودراسات قرآنية
Keywords: التعليل، القرآن، سورة النساء; Reasoning, Qur’an, An-Nisa